TheFuture of species under climate change:Resilience or decline? - Moritz Craig; Agudo Rosa (Science, 2013)
As climates change across already stressed ecosystems, there is no doubt that species will be affected, but to what extent and which will be most vulnerable remain uncertain. The fossil record suggests that most species persisted through past climate change, whereas forecasts of future impacts predict large-scale range reduction and extinction. Many species have altered range limits and phenotypes through 20th -century climate change, but responses are highly variable. The proximate causes of species decline relative to resilience remain largely obscure;however, recent examples of climate-associated species decline can help guide current management in parallel with ongoing search.
Keywords: Climate change